Human Placenta-derived Cells (PDA-001) for the Treatment of Moderate-to-severe Crohn's Disease: A Phase 1b/2a Study. Issue 8 (August 2015) - Melmed, Gil Y.; Pandak, William M.; Casey, Kevin; Abraham, Bincy; Valentine, John; Schwartz, David; Awais, Dahlia; Bassan, Issac; Lichtiger, Simon; Sands, Bruce; Hanauer, Stephen; Richards, Robert; et al.
Abstract : Background: PDA-001 (cenplacel-L), a preparation of placenta-derived mesenchymal-like adherent cells with immunomodulatory effects, previously demonstrated safety and tolerability in an open-label Crohn's disease (CD) study. The current phase 1b/2a study evaluated the safety and efficacy of PDA-001 in subjects with moderate-to-severe CD. Methods: Subjects had active inflammation on colonoscopy or elevated fecal calprotectin and inadequate response to conventional therapy. Concomitant therapy with stable doses of immunomodulators and/or biologics was permitted. Subjects received 8 units of PDA-001 (1.5 × 10 8 cells per unit) in the phase 1b open-label study. In the phase 2a double-blind study, subjects were randomly assigned placebo, 1 unit, or 4 units of PDA-001 (2 infusions 1 wk apart). The primary endpoint was induction of clinical response (≥100 points and/or 25% decrease in Crohn's Disease Activity Index) at 4 and 6 weeks. Results: Fifty subjects were enrolled (safety analysis, 50 subjects; efficacy analysis, 48 subjects). Four subjects received 8 units of PDA-001 (phase 1b study); 46 subjects were subsequently randomized to 1 or 4 units of PDA-001 or placebo (phase 2a study). The primary endpoint was achieved in 10/28 (36%) of PDA-001 subjects compared with placebo (0%, P = 0.026). Clinical remission was achieved in 4/28 (14%) of PDA-001 subjects compared with placebo (0%, P = 0.3). One treatment-related serious adverse event occurred (systemic hypersensitivity reaction at 8 units). In the phase 2a study, serious adverse events occurred in 9/28 (32%) of PDA-001 subjects and 1/16 (7%) of placebo subjects. Conclusions: A 2-infusion regimen of PDA-001 induced clinical response in subjects with moderate-to-severe CD. Additional studies are warranted. Abstract : Article first published online 15 May 2015.